Integrating digital comics into physical education: a new model for enhancing elementary athletic learning - Da'i, Mohamad; Apriyanto, Rohmad (Edu Sportivo: Indonesian Journal of Physical Education, 2025)
Background: By integrating interesting and interactive visualisations, digital comics are expected to help students to better understand the concept of athletic techniques and increase their interest in participating in lessons. This approach provides a solution to the challenges in learning basic athletics, which are often considered boring and difficult to understand by students. Research Objective: This research aims to develop digital comics as a learning tool in physical education to improve students’ understanding and basic athletic skills. Through interactive visual media, it is hoped that students will be more motivated and better understand the concepts. Method: This research uses the ADDIE method, which includes the stages of analysis, design, development, implementation, and evaluation.  The respondents of this study are class IV students at MI Plus Al-Fatimah Bojonegoro, totalling 42 students, consisting of 18 boys and 24 girls. The digital athletic comic was validated by 3 experts consisting of 1 media expert, 1 content expert, and 1 athletic practitioner. The results obtained were then analysed using the content validity index and content validity ratio. Finding/Result: The validation results by 3 experts that have been analysed show that the content validity index obtained an average score of 4.45, and the content validity ratio analysis showed an average score of 4.47. This shows that the digital comic model developed is very appropriate and relevant and meets the quality standards needed to increase student understanding and motivation in learning basic athletics. Conclusion: Digital comics have been shown to be effective as a learning tool to increase students' understanding, participation and motivation in basic athletics. For future research, it is recommended that the application of digital comics be extended to other subjects by involving larger groups. In addition, further research could examine the long-term impact of using digital comics on students’ academic achievement and motor skills.